Desenho inscrito no corpo - Eugenio Paccelli da Silva Horta (2010)
This work deals with the relationship between the experience and the understanding of his own body and its development in the practice of drawing and observation as an opportunity to maximize and offer other perspectives to students of art. Students who are sensitive to the origin of their own mobility and do not just consider the line and drawing, but its origin, thought to be held in a place of its own: their body. It is proposed that the formulation of lessons, creation of specific teaching methodologies and classroom activities are part of the demands of the always evolving and poetic experience of the artist/teacher. Journeying by authors such as Jorge Wagensberg, Michel Onfrey, Villén Flusser, Lucia Gouvêa Pimentel, Lina Bo Bardi, Georges Didi-Huberman, among others, is based on the actual practice of the artist/teacher and his development of theories consistent with each teaching objective.